Congress Responds to the Twentieth Century - Dewhirst, Robert E.; Ahuja, Sunil (Book collections on Project MUSE., 2003)
Congress occupies a central place in the U.S. political system. Its reach into American society is vast and deep. Overtime, the issues it has confronted have increased in both quantity and complexity. At the beginning, Congress dealt with a handful of matters, whereas today it has its hands in every imaginable aspect of life. It has attempted to meet these challenges and has changed throughout the course of its history, prodded by factors both external and internal to the institution. The essays in this volume argue therefore that as society changed throughout the twentieth century, Congress responded to those changes.